Analisis Penipuan Online Melalui Media Sosial Dalam Perspektif Kriminologi - M, Mulyadi; Nurdin, Aulia Anjani; Anjani, Axara Alejendra; Alamsyah, Fiqih Dien; Sifana, Firdha; Yudistio, Muhammad Albar; Maulana, Muhammad Kareem; Rabbani, Radiyya Alvaro Achmad (Media Hukum Indonesia (MHI), 2024)
Conventional fraud is regulated in detail in the Criminal Code along with its penalties. However, in modern times, the act of fraud has developed from being conventional to being carried out using technology or commonly referred to as online. The research method used in this research is the normative juridical method. The results of this study state that there are many concrete forms of online fraud that occur through various social media platforms or online shopping media, such as phishing, scamming, and social engineering. The criminal offence of online fraud is regulated in Law No. 19 of 2016 on the amendment of Law No. 11 of 2008 on Electronic Information and Transactions. Specifically contained in Article 28 paragraph (1) of the ITE Law which regulates the provisions of fraud by providing false information in electronic media, so that anyone who violates it has committed a criminal offence of fraud. The criminal provisions can be seen in Article 45A paragraph (1) of the ITE Law, which is a maximum imprisonment of (6) six years and/or a maximum fine of Rp. 1,000,000,000.00 (one billion rupiah). Efforts to prevent online fraud, namely the need to increase and improve the professionalism and integrity of law enforcement officials in handling cases of online fraud crimes that are rampant in the community. This is done so that there is legal certainty and guaranteed protection for the community.